Analisis Kebijakan Digitalisasi dan Teknologi dalam Pendidikan - Fatrisna, Yuli; Sesmira, Meli; Mudarti, Hasni; Rahmi, Sri (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to analyze digitalization and technology policies in education. This study uses a literature review approach to analyze policies related to digitalization and technology integration in education. This method involves systematically collecting, reviewing, and synthesizing relevant scientific articles, policy documents, and official reports published in the last decade. Data sources include peer-reviewed journals, books, government publications, and credible online repositories. Selection criteria are applied to ensure the inclusion of high-quality and relevant literature. The review is then followed by a thematic analysis framework to categorize the findings into key themes, such as policy objectives, implementation challenges, and impacts on educational outcomes. The results of the analysis show that the system and policies related to the implementation of the National Education Standards (SNP) in Indonesia, it can be concluded that SNP plays an important role as the main reference in efforts to improve the quality of education in all regions. To increase the effectiveness of the implementation of SNP, a more adaptive and contextual policy strategy is needed in accordance with the characteristics of each region. Strengthening the capacity of educators, improving educational infrastructure, and formulating policies that are more responsive to local dynamics are the top priorities in ensuring equitable distribution of national education quality